2010
DOI: 10.1017/s0260210510001208
|View full text |Cite
|
Sign up to set email alerts
|

Captured by the camera's eye: Guantánamo and the shifting frame of the Global War on Terror

Abstract: In January 2002, images of the detention of prisoners held at US Naval Station Guantanamo Bay as part of the Global War on Terrorism were released by the US Department of Defense, a public relations move that Secretary of Defense Donald Rumsfeld later referred to as 'probably unfortunate'. These images, widely reproduced in the media, quickly came to symbolise the facility and the practices at work there. Nine years on, the images of orange-clad 'detainees' -the 'orange series' -remain a powerful symbol of US … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Discourse analysts have shown that news reports are often framed to develop certain ideas over others by emphasising some aspects of an event while ignoring or making others invisible (Van Veeren ). Identifying such discrepancies between fiction and reality enables scholars to discern which objects or experiences are taboo and thus remain hidden from public view.…”
Section: Frame Analysis and Public Perceptions Of Dyingmentioning
confidence: 99%
“…Discourse analysts have shown that news reports are often framed to develop certain ideas over others by emphasising some aspects of an event while ignoring or making others invisible (Van Veeren ). Identifying such discrepancies between fiction and reality enables scholars to discern which objects or experiences are taboo and thus remain hidden from public view.…”
Section: Frame Analysis and Public Perceptions Of Dyingmentioning
confidence: 99%
“…Meanwhile, the cells were emptied of detainees. The tourist gaze tended to fall on “empty” spaces, which was important for constructing Guantánamo as “safe” and “humane” (Van Veeren ). In connection with the “hardening” of detention and warehousing, detainees were (re)cast as too dangerous to be seen or known (their identities kept secret) as part of the justification of detention's militarization.…”
Section: The Tourmentioning
confidence: 99%
“…As this article contends, these tours, and the photographic practices connected to them (Van Veeren ), were central to the Bush administration and US military's attempts to (re)constitute the United States as both a “safe” and “humane” actor and therefore manage the war both domestically and internationally. After failing to anticipate different readings of the camp's opening and the corresponding international backlash (not to mention the scandal of Abu Ghraib), the Bush administration and US military needed to shift perceptions of US detention practices, maintaining that Guantánamo, as the showpiece detention facility, was not only safe but also humane, legal, and transparent in its dealings with “enemy combatants.” They needed to demonstrate that the “people there are being treated far better than they expected to be treated by any other government on Earth” (Vice President Dick Cheney in Porteus ).…”
mentioning
confidence: 99%
“…While the GWoT and the Iraq War in particular have been studied for insights into new approaches to media in the prosecution of the war (Croft 2006;Hammond 2007;Martin and Petro 2006), in particular the use of 'milblogs' (Wall 2005), embedded journalists (Cottle 2006;Hiebert 2003), the rise of virtual warfare and merging of entertainment with news (Debrix 2008;Der Derian 2003Van Veeren 2009), the unique use of Guantánamo as a telegenic spectacle for constructing the reality of this war remains unexamined. Bringing a poststructuralist lens to Guantánamo, and in particular the works of Jean Baudrillard and James Der Derian, noted for their theorizing of modern warfare and the role of mediation and simulation, and applying a materialdiscursive analytic approach (Laclau and Mouffe 1987) to bear on the tourist practices associated with Guantánamo, this article argues that Guantánamo was a simulation used to produce a reality of war.…”
Section: Introductionmentioning
confidence: 99%